The Relationship Between Performance and Graphic Presentation in Unit Trusts' Annual Reports: Malaysian Evidence (Journal of Business Management and Accounting, 2011)
This study investigates the use and abuse of graphs in the annual reports of unit trust companies. It is found that 78% of companies use graphs and that 2.1 is the mean number of graphs per graph-using companies. The most commonly graphed financial variables are asset allocation, performance, investment and fund size. Line and pie graphs are more popular than bar and column. Thus, in contrast to previous studies of graphs in annual reports, no relationship is found between performance and graphic presentation in unit trusts' annual reports. The result may suggest that graphic presentation in unit trust's annual report is normally dependent on the discretion of the company's management.